Visions of the End in Medieval Spain : Catalogue of Illustrated Beatus Commentaries on the Apocalypse and Study of the Geneva Beatus - Williams, John, 1928 February 25-2015 (Book collections on Project MUSE., 2017)
"This is the first study to bring together all twenty-nine extant copies of the medieval Commentary on the Apocalypse, which was originally written by Spanish monk Beatus of Liebana. John Williams, a renowned expert on the Commentary, shares a lifetime of study and offers new insights on these strikingly illustrated manuscripts. As he shows, the Commentary responded to differing monastic needs within the shifting context of the Middle Ages. Of special interest is a discussion of the recently discovered Geneva copy: one of only three commentaries to be written outside of the Iberian Peninsula, this manuscript shows both close affinities to the Spanish model and fascinating deviations from it in terms of its script and style of illustrations"--Publisher.